Will agriculture always remain a problem in GATT? - Stefan Tangermann (Intereconomics, 1987)
GATT has had extraordinarily scant “success” in the agricultural sphere up to now. To what extent is this due to the special status accorded to agriculture in GATT? Are trends discernible within GATT that might lead to an improvement in the situation? Might the Uruguay Round produce fundamentally new solutions?
Keywords: 330; Protectionism